Penguatan Kader Masyarakat Dan Puskesmas Dalam Pelaksanaan Deteksi Dini Penyakit TB Paru Di Desa Tambakbaya, Cibadak Kabupaten Lebak Banten - Dini Syafitri; Agus Riyanto; Atang Saputra; Dea Syakilla Syafitri; Yunda Nurmala Septianti; Ega Arfanza (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Mycobacterium tuberculosis is the bacterium causing tuberculosis, which can affect the lungs. In 2012, Banten Province reported 7,327 cases per 100,000 population of pulmonary TB. In Lebak Regency, 115 children had TB at Mandala Community Health Center in Cibadak District. According to the Ministry of Health, TB control efforts include health promotion, TB surveillance, risk factor control, case finding and management, immunization, and preventive medication. Poor environmental conditions can increase TB transmission risks, necessitating prevention and management measures. Preventive actions include maintaining cleanliness and humidity in homes, regularly opening doors and windows for air circulation, allowing sunlight to enter, and covering the mouth when coughing. The objective of this activity is to enhance the knowledge and attitudes of health volunteers, the community, and health centers in early detection of pulmonary TB in their environments. Methods used include lectures, discussions, and quizzes to assess participants' understanding. This community service activity was conducted in June 2024. The outreach results showed an increase in knowledge about pulmonary TB prevention among participants. The community and health volunteers gained a better understanding of the disease.